A case of immune complex type hemolytic anemia induced by initial micafungin administration. (September 2022) - Ishii, Hiroto; Sato, Tomohiko; Ishibashi, Miyuki; Yokoyama, Hiroki; Saito, Takeshi; Tasaki, Tetsunori; Yano, Shingo
Highlights: Initial micafungin administration can cause immune complex type hemolytic anemia. A man developed immune complex type hemolytic anemia by initial micafungin administration. The direct anti-globulin test and the immune complex test confirmed the diagnosis. Prompt cessation of micafungin served as a successful treatment. Abstract: We report the first case of immune complex type hemolytic anemia by initial micafungin administration that was given as prophylaxis to a 42-year-old Japanese man receiving chemotherapy for primary amyloidosis. The few cases found in the literature were associated with secondary administration causing immune hemolytic attacks. Despite its rarity, the present case calls for increased awareness of micafungin-induced hemolytic anemia upon initial administration.